PENGARUH INTELECTUAL CAPITAL TERHADAP PRODUKTIVITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Novaliastuti Masiaga (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
This research aims to analyze intellectual capital effect on productivity. The independent variable in this research is Intellectual Capital which is measured by using the VAICTM Method with three measurement indicators namely VACA (value added capital employed), VAHC (value-added human capital) and SCVA (structural capital value added). The dependent variable in this research is Productivity measured by using ATO (Asset Turn Over) Method of collecting data collected using the literature study method and documentation. Literature study is done by processing literature, articles, journals and other written media relating to the topic of discussion of this research. This research uses secondary data, namely Annual financial report that was published by a company in the Indonesia Stock Exchange. The population in this research is manufacturing companies listed on the Indonesian Stock Exchange during the period 2012 – 2016. By using purposive sampling method, the total of a sample in this research is 10 companies. Data analysis method uses simple and multiple linear regression. The results of this research indicate that Intellectual Capital, VACA (value added capital employed), VAHC (value-added human capital), and SCVA (structural capital value added) does not have a positive effect on company productivity